IMPACT OF ZN-DOPPED ON SNEDDS/ZNXFE3-XO4 FORMULATION ON THEIR CRYSTAL STRUCTURE AND ANTIOXIDANT PERFORMANCE - Zahira, Uvia Ardina; Chusna, Nadiya Miftachul; Taufiq, Ahmad; Sunaryono, Sunaryono (Universitas Mataram, 2025)
Self-Nano-Emulsifying Drug Delivery System (SNEDDS)/ZnxFe3-xO4 has been successfully formulated through the synthesis of ZnxFe3-xO4 by the coprecipitation method and SNEDDS/ZnxFe3-xO4 by the sonication method. This study is focused on the effect of Zn doping on the crystal structure and antioxidant performance ofÂ ZnxFe3-xO4 nanoparticles. ZnxFe3-xO4 samples were characterized using FTIR and XRD to determine the functional groups and structure of the sample, respectively. SNEDDS/ZnxFe3-xO4 samples were characterized using FTIR and Antioxidants with the DPPH method to determine the functional groups and antioxidants in the sample, respectively. The FTIR characterization results of the ZnxFe3-xO4 sample showed the emergence of Zn-O and Fe-O functional groups in the wave number range of 825-869 cm-1 and 560-594 cm-1, respectively. This indicates that Zn2+ doping was successfully synthesized and shifted the Fe3+ ion. The IR spectrum also shows that the higher the concentration of Zn2+ ions, the more significant the change in absorption intensity, indicating that more molecules absorb light at wave numbers of 825-869 cm-1. The XRD characterization results show that the ZnxFe3-xO4 nanoparticle structure is an inverse cubic spinel occupying the Fd3m crystal group. Based on the analysis of XRD data, the higher the concentration of Zn2+ doping, the smaller the size of the ZnxFe3-xO4 nanoparticles produced. The diffraction peak of the sample on the 311 plane shifts towards a smaller angle due to the effectiveness of Zn2+ ion doping, shifting the Fe3+ ion because the radius of the Zn2+ ion is larger than the Fe3+ one. The antioxidant performance analysis of SNEDDS/ZnxFe3-xO4 showed inhibition potential ranging from 11% to 15%, increasing with higher ZnÂ²âº concentrations.